Ti3C2Tx (MXene) disrupts growth and development in Daphnia magna by suppressing related genes and inducing gut microbiome dysbiosis - Xiang, Qianqian; Wu, Yanping; Li, Yongfang; Li, Shaoxiang; Chang, Xuexiu (Frontiers in Microbiology, 2026)
The potential risks of Ti3C2Tx (MXene) nanomaterials to the ecological environment and human health have drawn increasing attention due to their widespread applications in the fields of biomedicine and environmental remediation. Although the aquatic ecotoxicity of Ti3C2Tx has been reported, little is known about how Ti3C2Tx disrupts the physiological processes that regulate growth and development in zooplankton. This study investigated the toxic effects and mechanisms of Ti3C2Tx exposure on the growth and development of Daphnia magna through gene expression and gut microbiome analyses. Results show that Ti3C2Tx exposure significantly reduced moulting frequency, body length, body width, and absolute growth rate in D. magna. Exposure to Ti3C2Tx led to a significant decrease in the expression of growth and development-related genes (cyp18a1, ecra, usp, hr3, and cpa1) in D. magna. Microbiome analysis revealed that exposure to Ti3C2Tx resulted in a decrease in Proteobacteria and an increase in Bacteroidota in the microbial community of D. magna. Meanwhile, Ti3C2Tx induced reduced abundances of Pseudomonas and Aeromonas, as well as increased abundances of Bacillus and Phascolarctobacterium. These microbial functions primarily contribute to energy acquisition and metabolism. This study indicated that Ti3C2Tx can inhibit the growth and development of D. magna by inhibiting the expression of growth and development-related genes and inducing intestinal microbial community dysbiosis. This study provides new insights into understanding the mechanisms of Ti3C2Tx toxicity on the growth and development of zooplankton in aquatic ecosystems.